Community Attitudes about Discussing Sexual Health: Assessing Public Opinion of Local STD Prevention Campaigns. (March 2013) - Thomas, Rosalind; Homawoo, Brigitte Bekan; McClamroch, Kristi; Wise, Benjamin; Coles, F. Bruce
Objectives: We assessed public views about the acceptability of and need for sexually transmitted disease (STD) and sexual health-related educational messaging in local campaigns. Methods: A 28-item state-added module was included in the 2008 New York Behavioral Risk Factor Surveillance System survey ( n =3, 751). Respondents rated acceptability of venues/dissemination channels and messaging and agreement with attitudinal/need statements. Additional data were analyzed from a separate state survey with individual county samples ( n =36, 257). We conducted univariate, bivariate, and multivariable modeling analyses. Results: Each venue was acceptable to more than three-quarters of respondents (range: 79% for billboards to 95% for teaching STD prevention in high school). All message areas were acceptable to at least 85% of respondents (acceptability rating range: 85% to 97%). More than 70% agreed that there is a need for more open discussion about STDs. Bivariate analyses identified areas where messaging tailored to specific subgroups may be helpful (e.g., 26% of white people, 44% of African Americans, and 45% of Hispanic people agreed with the statement, "I need ideas about how to talk to my partner about protection from STDs"). Little geographic variation was seen. Results of multivariable modeling on opposition showed limited interaction effects. Conclusion: These data provide key information about current community norms and reflect the public's approval for hearing and seeing more about sexual health and STDs in a range of public forums.